Functional chrematonyms of dialectal base as a commercial way of gaining regional recipient - Łuc, Izabela (Papers in Linguistics, 2020)
The article concerns the role of dialect-based functional chrematonyms in the process of attracting the regional (Upper Silesian) recipient. Not much attention has so far been paid to the meaning of the names in this category so, thus it has become the subject of the research. The article aims 1) to describe the commercial ways (model) of translocating functional-categorical aspects of local dialect into the naming sphere; 2) to point out the structural-semantic naming variants, together with an attempt to determine the phenomena and changing tendencies related to naming acts. The study focused on two subcategories of functional chrematonyms: ideational and social ones; occasionally, some other naming types beyond this classification were mentioned. The semantic-functional analysis of names shows that in naming processes the Upper Silesian local dialect is exploited as a valuating onymic tool and that some dialectal lexemes (bajtel, gryfny, maszkety) are extremely popular. These dialectalisms 1) evaluate names, and as elements of collocations with other units of language create commercial terms with clear meanings for local recipients and 2) evaluate the Upper Silesian sphere and the microcommunity which lives there. The extraordinary popularity of these lexemes in the naming acts allows one to speak about the repeatability of creating scheme and about the phenomenon of onymic fashion for dialectal units.